Applications of General Residual Power Series Method to Differential Equations with Variable Coefficients - Bochao Chen; Li Qin; Fei Xu; Jian Zu (Discrete Dynamics in Nature and Society)
This paper is devoted to studying the analytical series solutions for the differential equations with variable coefficients. By a general residual power series method, we construct the approximate analytical series solutions for differential equations with variable coefficients, including nonhomogeneous parabolic equations, fractional heat equations in 2D, and fractional wave equations in 3D. These applications show that residual power series method is a simple, effective, and powerful method for seeking analytical series solutions of differential equations (especially for fractional differential equations) with variable coefficients.